Determinant domain in prognosis evaluation of the septic patient in the intensive care unit. - Alexis Díaz Mesa; Rubén Bembibre Taboada; Alexis Suárez del Villar Labastida; Dagmaris Losa Pérez (Medisur)
Background: Sepsis is the most frequent cause of death in critical ill patient. The necessity to have with evolutionary and predictable markers for medical routines is a tangible fact. Objective: To make a study about the determinant supremacies in the assessment and prognosis help of the patient whose main complaint of admission in the ICU was sepsis. Methods: A descriptive, retrospective, longitudinal and series of cases study (N=155, n=127) with polytomic logistic regression was carried out in order to determine the essential supremacies by means of V Cramer’s, Rho Spearman’s and Pearson R. Results: The essential supremacies for the evolution and prognosis were identified including clinical, paraclinical aspects and some others which in a decrement order by correlations coefficient analyzed were the following: Hb < 80 gr / L, glycemia >12 mmol / L, time of bleeding >4 seconds, SAT < 80 mmHg, HR >101 beats / min, creatinine >200 mmol / L, platelet count <100 000 / L, K+ >6 mEq / L and the levels of PH < 7.15, all of them at the 5th day of evolution, and the multiple organic dysfunction. Conclusions: To evaluate important clinical, paraclinical and some others supremacies in a continuous form in the attention of septic patients in our intensive care units is a great help in the evolution, and the establishment of the prognosis in our patient making such an inference by measures made at the 5th day of the assessment.